Fundamental Problems of Federal Income Taxation - Adams, Thomas S. (Quarterly Journal of Economics, 1921)
The problem: what is the sound and enduring solution of the tax problem? I. The surtaxes. (1) The surtaxes excessive. Their declining yield, 529. — (2) Tax-free securities, 530. — (3) Can the leaks be stopped, 532. — (4) Tax morality, 536. — (5) Theory of surtaxes, 537. — (6) The scientific solution, 539. — The immediate solution, 540. — II. Income taxes on corporations and business. (8) The income tax as a producer's or business tax, 541. — (9) Relation between personal and business income taxes, 542. — (10) The proposed corporation surtax, 544. — III. Basis of the Business Tax, 548. — (11) Shifting, 548. — (12) Simplicity versus equity, 551.